Unresponsive wakefulness or coma after cardiac arrest—A long-term follow-up study. (October 2018) - Petzinka, Victor N.; Endisch, Christian; Streitberger, Kaspar J.; Salih, Farid; Ploner, Christoph J.; Storm, Christian; Nee, Jens; Leithner, Christoph
Abstract: Objective: To investigate the clinical course and early prognostic markers in cardiac arrest (CA) patients discharged from the intensive care unit (ICU) in an unresponsive wakefulness syndrome (UWS) or coma. Methods: 89 patients were identified from a prospective CA database. Follow-up was conducted by telephone interviews with legal guardians, evaluation of re-admission and rehabilitation reports assessing core elements of the coma recovery scale-revised (CRS-R). Somatosensory evoked potential (SSEP) and electroencephalography (EEG) original recordings were re-analyzed, the gray-white-matter ratio (GWR) was determined from brain computed tomography (CT) and neuron-specific enolase (NSE) serum concentrations were retrieved. Results: Follow-up was successful for 32/50 (64%) patients admitted between 2001–2009 and 31/39 (79%) between 2009–2015. Median ICU stay was 27 days (IQR 20–36). Neurological improvement beyond UWS was found in 2 of 63 patients. Among 61 patients with successful follow-up and no improvement, NSE serum concentrations within the reference range, SSEP amplitudes above 2.5 μV or continuous reactive EEG were found in 5%, 3% and 2% of those tested. NSE > 90 μg/L, SSEP ≤ 0.3 μV, highly malignant EEG or GWR < 1.10 were found in 44%, 49%, 35% and 22% of those tested. Conclusions: Neurological recovery was rare in CA patients discharged in UWS after prolonged ICU treatment. Status epilepticus requiring prolonged deep sedation is one potential reason for delayed awakening. Sensitivity for established poor outcome parameters to predict persistent UWS early after CA was moderate. SSEP, EEG and NSE may indicate absence of severe HIE early after CA.